Circular RNA SMARCA5 is overexpressed and promotes cell proliferation, migration as well as invasion while inhibits cell apoptosis in bladder cancer - Tan, Yiao; Zhang, Tengyue; Liang, Chaozhao (Translational Cancer Research, 2019)
Background: This study aimed to investigate the function of circular RNA SMARCA5 (circ-SMARCA5) on cell proliferation, apoptosis, migration and invasion in bladder cancer. Methods: Ten pairs of human bladder cancer tissue and adjacent tissue, five human bladder cancer cell lines (including TCCSUP, 5637, J82, UM-UC-3 and T-24) and normal human urothelial cell line SV-HUC-1, were obtained for the detection of circ-SMARCA5. Control overexpression and ShRNA, circ-SMARCA5 overexpression and ShRNA were constructed and transfected into UM-UC-3 cells as Control(+), Control(−), Circ-SMARCA5(+) and Circ-SMARCA5(−) groups. The role of circ-SMARCA5 was investigated in terms of cellular proliferation, apoptosis, migration, and invasion. Results: Circ-SMARCA5 was overexpressed in tumor tissue compared to paired adjacent tissue and it was also overexpressed in TCCSUP, 5637, J82 and UM-UC-3 cells compared to normal human urothelial cell line SV-HUC-1. In UM-UC-3 cells, cell proliferation ability, migration rate and invasion cell count were increased in Circ-SMARCA5(+) group compared to Control(+) group, while reduced in Circ-SMARCA5(−) group compared to Control(−) group. Regarding the cell apoptosis, apoptosis rate and apoptotic protein C-Caspase 3 expression were decreased in Circ-SMARCA5(+) group than those in Control(+) group but raised in Circ-SMARCA5(−) group compared to Control(−) group, meanwhile, the anti-apoptotic protein Bcl-2 expression was elevated in Circ-SMARCA5(+) group than that in Control(+) group but reduced in Circ-SMARCA5(−) group compared to Control(−) group. Conclusions: Circ-SMARCA5 is overexpressed, and promotes cell proliferation, migration and invasion, but represses apoptosis in bladder cancer.